Cows, Sheep & Scots: Livestock and Immigrant Strategies in Rural Upper Canada, 1814-1851 - Ritchie, Elizabeth (Ontario History)

(untitled) (The Ontario Historical Society, 2017)
In the ongoing discussion of how Canada’s economy developed and how the land was colonised, little attention has been paid to the role of farm animals. The strategies of Scottish immigrants to rural Upper Canada show the centrality of livestock in subsistence, in the informal economy of barter, exchange and credit, and in off-farm sales. Raising stock—particularly cattle, sheep and pigs—was not an addition to settlers’ sources of income and subsistence, but underpinned most of them. Letters back to Scotland, supplemented by surveys and census data, show that animals’ contribution to clearing forest, raising crops, maintaining soil, providing food and clothing, raising cash or credit, maintaining reciprocal relationships and passing on property was integral to the success of backwoods farmers as they strove first for survival, and then for comfort.